143k views
4 votes
HERES THE QUESTION xD ( this is only one )

f ( x ) = 9 x^3 + 2 x^2 − 5 x + 4 and g ( x ) = 5 x^3 − 7 x + 4 . what is f ( x ) − g ( x ) ? Show all of your steps and write your final answer in factored form.

User Nijas
by
5.8k points

2 Answers

2 votes

Answer:


\large\boxed{f(x)-g(x)=4x^3+2x^2+2x}

Explanation:


f(x)=9x^3+2x^2-5x+4,\ g(x)=5x^3-7x+4\\\\f(x)-g(x)=(9x^3+2x^2-5x+4)-(5x^3-7x+4)\\\\=9x^3+2x^2-5x+4-5x^3-(-7x)-4\\\\=9x^3+2x^2-5x+4-5x^3+7x-4\qquad\text{combine like terms}\\\\=(9x^3-5x^3)+2x^2+(-5x+7x)+(4-4)\\\\=4x^3+2x^2+2x

User Gypaetus
by
6.5k points
3 votes

Hello

f(x)= 9x^3+ 2x^2 -5x+ 4

g(x)= 5x^3 -7x+ 4

f(x) - g(x)

= (9x^3+ 2x^2 -5x+ 4) - (5x^3 -7x+ 4)

= 9x^3+ 2x^2 -5x+ 4 -5x^3+ 7x -4

= (9x^3 -5x^3)+ 2x^2+ (7x -5x)+ (4-4) (combine like terms)

= 4x^3+ 2x^2+ 2x

= 2x* (2x^2+ x+ 1)

The final answer is 2x* (2x^2+ x+ 1).

I hope this helped! ;)

User Colen
by
6.6k points